Properties of toxin-resistant sodium channels produced by chemical modification in frog skeletal muscle. - Spalding, B C (1980)
1. Single skeletal muscle fibres from the frog Rana pipiens were treated with the carboxyl group modifying reagent trimethyloxonium ion (TMO) and voltage clamped by the method of Hille & Campbell (1976). 2. TMO treatment reduced current through sodium channels to 0.33 +/- 0.03 that before treatment, but only 45 +/- 3% of this remaining current was blocked by 1 microM-tetrodotoxin (TTX) and only 37 +/- 5% by 100 nM-saxitoxin (STX). 3. This toxin resistance persisted in 90 microM-TTX, was not due to inactivation of toxin nor to components of the reaction solution other than TMO, but was prevented by the presence of 100 nM-STX during treatment with TMO. TMO-modified sodium channels can be blocked by the local anaesthetic lidocaine. 4. The permeabilities of TMO-modified channels to hydroxylammonium, ammonium, guanidinium, aminoguanidinium, methylammonium and tetramethylammonium ions relative to sodium were not significantly different from the permeabilities of untreated sodium channels. 5. Hydrogen ions blocked TMO-modified sodium channels, but the apparent pKa for block at +38 mV of 5.07 was significantly less than the corresponding value of 5.32 in untreated sodium channels. 6. It is suggested that TMO produces toxin resistance by esterifying an ionized carboxyl group which is an essential part of the toxin binding site. Such esterification would electrostatically reduce the local cation concentration, thus reducing the apparent pKa of hydrogen ion block and the single-channel conductance (Sigworth & Spalding, 1980). 7. It is concluded that the sodium channel contains a second acid group, near but distinct from an acid group previously hypothesized to be part of the selectivity filter and hydrogen ion binding site (Hille, 1971, 1972, 1975a).